(untitled) (2018)
In this study, samples from four different sites were collected from Río Frío, a stream crossing the city of Bucaramanga (Colombia). The course evaluated started in the suburban area and finished in the vicinity where Río Frío becomes the tributary of Río de Oro. Invertebrates were identified belonging to different phyla: Annelida, Mollusca, and Arthropoda, corresponding to five classes, 14 orders, and 51 families. Biological monitoring working party (BMWP)/Col., ICO, and ICA-CETESB (Environmental Agency of the State of São Paulo) indexes were evaluated to determine water quality and environmental impact caused by urban growth. Statistical analysis of collected data revealed progressive basin deterioration from the first site of collection to the last site. At the beginning of the evaluated course, good water quality was observed. However, after flowing through the urban area, very poor quality indexes were detected. Based on the Wenger et al. guidelines two main problems were identified: weak enforcement of environmental laws, in addition to poorly legislated environmental urban planning.